THE IMPLEMENTATION OF CHARACTER EDUCATION THROUGH LEARNING OF ISLAMIC RELIGION EDUCATION IN MUHAMMADIYAH SCHOOL IN INDRAMAYU DISTRICT (IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MUHAMMADIYAH DI INDRAMAYU) - ALI MIFTAKHU ROSYAD (al-Afkar, 2019)
This study is aimed to identify (1)the planing of character education in Islamic studies; (2) the implementing of character education in Islamic studies; and (3) the evaluating of character education in Islamic studies. The study was pursued the qualitative research with kind of case study.  The subjects were the principal, teachers, and students. The determination of the subjects was done by using the purposive technique by selecting a number of respondents who are tailored to the purpose of this research. The data were collected through non-participant observation, in-depth interviews and documentation. The technique of data analysis refers to the steps of data analysis proposed by Mills and Heberman with interactive models. The results showed that (1) in the process of planning the school has the development program of school culture to implement student character values which actualized through  learning activities; (2) in the implementation of character education actualized by giving good example, admonition, notification, punishment, and task; and (3) based on assessing result showed that  the character values that have been actualized in the daily behavior of the students of Muhammadiyah School in Juntinyuat are democracy values, religious, cooperation, social care, respect/honor, and responsible. This study is expected to provide contributions for social studies teachers in Indramayu district as an actualization internalization of character values through school culture.